Barriers and Challenges af Information Technology in Labour Intensive Business Organization - Faizal, Muhammad; Lucky Nara, Maskarto; Nurdiyanto, Heri (International Journal of Engineering and Technology, 2018)
Information technology in the era of globalization and business competition plays a vital role in the sustainability of business organizations. Human resources owned by management must be managed well in order to have the competencies required by the company and as a power to produce quality products. In this study, the main problem is how the application of information technology to business organizations in Indonesia and what are the obstacles and challenges in its form. From these problems, the purpose of this study is to determine the application of information technology to business organizations as well as barriers and challenges it faces. From the results of research conducted on 20 business organizations that exist in Bandung regency, obtained data as follows: 2 companies have applied information technology, 4 companies are already utilizing information technology, and 14 companies still rely on the power of human resources. The main obstacle that he faced was related to the quality of his human resources (competence) and financial. While the challenge is related to the global economic situation, there will be a reduction of employees, as well as marketing of production.Â Â